Case Report: Clinical, molecular, and functional characterization of autoimmune lymphoproliferative syndrome—a family study with a multimodal diagnosis - Guido, Bruna Cândido; Camargo, Ricardo; Silva, Caroliny Victoria dos Santos; Dias, Anna Carolina Silva; de Pontes, Robéria Mendonça; Santos Júnior, Agenor de Castro Moreira dos; Toscano, Raquel Alves; Tavares, Fabíola Scancetti; Antunes, Alexandre de Albuquerque; de Melo, Karina Mescouto (Frontiers in Pediatrics, 2025)
Autoimmune Lymphoproliferative Syndrome (ALPS) is a rare immunological disorder caused by defective apoptosis, commonly due to pathogenic variants in the FAS gene. We report a comprehensive clinical, immunophenotypic, molecular, and functional evaluation of nine members of a consanguineous Brazilian family harboring the pathogenic FAS (NM_000043.6:c.748C > T) variant. The index case, an 11-year-old boy, presented with recurrent cytopenias, splenomegaly, and increased double-negative T cells. Genetic analysis identified additional variants in CASP10 (NM_032977.4:c.1202_1208del), and LRBA (NM_001364905.1:c.2450-7C > T), evidencing a complex genotype. Functional assays confirmed different levels of impaired FAS-mediated apoptosis in some affected individuals. Among nine family members studied, four out them met clinical and molecular criteria for ALPS, demonstrating incomplete penetrance and variable phenotype. All affected individuals share the same variants in FAS and CASP10, yet their clinical presentations differ significantly. Clinical manifestations and elevated double-negative T cells were observed exclusively in male individuals. Notably, a female family member harboring both FAS and CASP10 variants remained asymptomatic, supporting previous findings of incomplete penetrance and suggesting that sex-related factors—possibly including hormonal influences—may modulate clinical expression in ALPS. Introduction of sirolimus therapy led to sustained remission in the index case. This study report a successful integration of multimodal diagnostic strategy for accurate identification and management of ALPS, and it highlights the potential role of targeted therapies in improving outcomes.